O uso de aplicativos no ensino remoto on-line de matemática no ensino médio durante a pandemia covid-19: uma revisão sistemática das dissertações do PROFMAT - Couto, Aldney Barbosa (2024)
The COVID-19 pandemic, a disease caused by the coronavirus, named SARS-CoV-2, has severely impacted the work of teachers. The suspension of face-to-face classes, as a preventive measure to the spread of the coronavirus, "pushed" the teaching professional to online remote work, where the mediation of the teaching and learning process often took place through application software, the "apps". With this research, we investigated and analyzed the teaching work carried out through online remote teaching through application software and developed in the area of mathematics with high school students during the COVID-19 pandemic. Therefore, our research, with a qualitative approach, with an exploratory purpose and bibliographic and documentary design, relied on the systematic review of the PROFMAT dissertations produced in the years 2020, 2021, 2022, and that deal with the use of applications in online remote teaching of high school mathematics. From the collection and analysis of the data, we found that teachers around Brazil mediated the teaching and learning process, mainly through the Google Meet and WhatsApp applications, for the realization of synchronous virtual classes and sharing of digital files. However, the research also shows a variety of other applications complementing the work in remote classes, and also account for the challenges and successes found by these teachers in working with Digital Information and Communication Technologies (TDICs), in addition to pointing out the support initiatives and regulation of teaching work during the non-face-to-face class regime.